2018
DOI: 10.1541/ieejjia.7.351
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Linear Synchronous Generator and Examination of the Driving Range for a Free-Piston Engine Linear Generator System

Abstract: A free-piston engine linear generator (FPEG) system is a linear generator, which generates electricity when a free piston reciprocates the combustion thrust produced by internal combustion. It is expected that this system can be applied to hybrid vehicles. In an FPEG system, the high combustion energy is instantly added to a free piston. Nevertheless, it is difficult for a linear synchronous generator (LSG) to convert combustion energy into electric energy by using the output of the LSG given the limit of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…leads to a large back electromotive force. To bring it within the control range of the PWM inverter, the voltage of each phase e must satisfy (5) considering the DC‐link voltage V dc . The phase‐induced voltages of each phase of the synchronous generator are given by (6)–(8), which are proportional to their respective speeds.…”
Section: Regenerable Range In the Low‐speed Areamentioning
confidence: 99%
See 1 more Smart Citation
“…leads to a large back electromotive force. To bring it within the control range of the PWM inverter, the voltage of each phase e must satisfy (5) considering the DC‐link voltage V dc . The phase‐induced voltages of each phase of the synchronous generator are given by (6)–(8), which are proportional to their respective speeds.…”
Section: Regenerable Range In the Low‐speed Areamentioning
confidence: 99%
“…The stator is a cylindrical structure that improves the energy density. In addition, the armature coil has concentrated winding to reduce the armature resistance, and this coil consists of a rectangular wire to increase the space factor . To concentrate the magnetic flux to the stator side, we used the Halbach array as permanent magnets of the mover.…”
Section: Regenerable Range In the Low‐speed Areamentioning
confidence: 99%
“…High efficiency is achieved using a linear generator that uses permanent magnets with a Halbach structure [17,18]. A cylindrical linear generator has been designed for the free piston, and the output density has been improved for automobiles [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…8 Continuous operation of a Free Piston Expander (FPE) linear generator in a waste heat recovery application has presented in the study of Tian et al, 9 which the feasibility working of the presented FPE linear generator has been confirmed by obtained results. A finite element method (FEM) analysis of static thrust and magnetic flux density distribution for a 10 kW, LSG, which has an efficiency of 97% for an FPEG application is presented in the study of Yamanaka et al 10 Initial design and electromagnetic field analysis based on ANSYS Maxwell for a Tubular Linear Generator (TLG) with radial and axial PM in free piston engines is discussed in the study of Subramanian et al 11 In this study, flux density, Back-EMF of the proposed machine have investigated, and the obtained results showed that the machine with axial PM provides extra output power and efficiency in comparison with the machine with radial PM. A FEM-based static thrust and magnetic flux density distribution of a novel FPEG configuration, which is applicable for hybrid vehicles, is presented in the study of Yamanaka et al 12 In the previous studies, 13,14 an improved flux path Homopolar BLDC generator has been investigated in which PM is replaced by a direct current excited auxiliary field winding to control the main magnetic flux pass through the machine.…”
Section: Introductionmentioning
confidence: 99%